O cotidiano no vale dos vinhedos: uma compreensão a partir das representações sociais - Paulus, Beatriz (Universidade do Vale do Rio do Sinos, 2009)
The present study is about Vineyard Valley, with social representations intake. The search focuses three territories: Bento Gonçalves, Monte Belo do Sul and Garibaldi, formers of a territorial cooperation of borders agreed around Vineyard Valley Wine Geographical Indication, which attribute to it development selectivity inherent to post modern societies, where entrepreneurship aggregates valuation nuances about the local production, which are translated into experiences, knowledge and actions, reinterpreted here through Social Representations. This way, knowing about these people interaction with tradition and the inherited culture from Italian ancestors is very important to maintain historical and cultural links. For this, it is used bibliographical search, ethnographic study, a field diary, participant observation, interview techniques and focal groups, among others, which result in an eight-dimension analysis: the socialized imaginary and immigration myths; religiosity; survival economy; structuring patria
Keywords: ciências sociais; psicologia social; representações sociais; uva; Vale dos Vinhedos; vinho; cotidiano; grape; social representations; social psychology; social science; Vineyard Valley; wine; daily; Ciências Sociais Aplicadas